2015
DOI: 10.1158/1055-9965.epi-13-1375
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with Biobank Participants: Preferences for Receiving and Providing Updates to Researchers

Abstract: Background Research biobanks collect biological samples and health information. Previous work shows that biobank participants desire general study updates, but preferences regarding the method or frequency of these communications have not been explored. Thus, we surveyed participants in a long-standing research biobank. Methods Eligible participants were drawn from a study of patients with personal/family history suggestive of Cowden syndrome, a poorly-recognized inherited cancer syndrome. Participants gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…These findings reinforce contributor privacy concerns as an important element of biobank communication and governance practices [60][61][62]. CAB members' varying preferences and uncertainty about the use of online tools and their desire for clear messages are also consistent with recent studies on biobank communication [17,63]. Some responses of CAB members could be characterized as a version of the therapeutic misconception.…”
Section: Meta-consentsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings reinforce contributor privacy concerns as an important element of biobank communication and governance practices [60][61][62]. CAB members' varying preferences and uncertainty about the use of online tools and their desire for clear messages are also consistent with recent studies on biobank communication [17,63]. Some responses of CAB members could be characterized as a version of the therapeutic misconception.…”
Section: Meta-consentsupporting
confidence: 81%
“…In contrast to principled concepts dominant in the bioethics literature, these notifications were not viewed by CAB members primarily in terms of increasing research transparency, but as reflecting a variety of values. Although no systematic review of biobank communication has been reported, some communication efforts by biobanks appear more common, including websites and newsletters [14][15][16][17]. As research obligations to disclose health-related results are ethically debated, the dissemination of both aggregate and individual results is also becoming more common [47][48][49][50][51][52].…”
Section: Meta-consentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if research clinics or networks maintain a website that provides information on completed studies, as is done in this clinic, participants could be notified when relevant information has been uploaded. Similarly, other studies have found that participants would like to receive paper or e-mail newsletter updates (Mester et al, 2015). While such information is available in the clinic where this research was conducted, participants generally did not realize this, indicating that the direct communication provided by a notification, e-mail, or newsletter may be more effective than uploading study results on a website where they may not be accessed.…”
Section: How To Return Resultsmentioning
confidence: 84%
“…Despite the wide range of electronic and online communication options available for cancer risk communication, our study found a high preference for print communication for both Hispanic and non-Hispanic women. Other research has found that participants in a biobank study preferred to receive yearly updates via convenient, inexpensive methods such as newsletters (Mester et al 2015). Randomized trials have found that print materials can be combined with telephone or in-person counseling to help increase access genetic risk information and services and promote informed decisionmaking (Kinney et al 2014a, b;Steffen et al 2015), but these trials did not include a large proportion of Hispanics or members of other underserved minority groups.…”
Section: Discussionmentioning
confidence: 99%